Sweet haven - McCoy, Shirlee (Zebra Books, 2016)
Neighbors who care, a peaceful routine--accountant Adeline Lamont is glad some things about her beloved hometown never change. But when her grandfather is injured, she has to run the family store, Chocolate Haven, and make its legendary fudge. Trouble is, she can't get the recipe right to save her life--or Chocolate Haven. And she doesn't need her ornery new tenant, Sinclair Jefferson, stirring up the pot with his help--and daring Addie to taste her wild side. Once Sinclair gets his hapless brother back on track, he's leaving Benevolence for good this time. He's made his life far away from his irresponsible family and their scandals. Trouble is, he can't quite stay away from Addie's optimism, enticing plus-size curves, and kindness to those who need it most. But they don't seem to have a thing in common--except that Addie's passion for chocolate, and for Benevolence, is just as contagious as Sinclair's passion for her. Maybe small-town life has its charms after all.